Corporate Social Responsibility and Students’ Internship: Analysis of Public Administration Students’ Internship In Private Companies (Journal of Governance and Development (JGD), 2012)
Internship is one of the efforts to prepare students in facing future employment. Some internships are held in private companies. From the point of view of the corporations or companies, the internship program can be included in corporate social responsibility (CSR) as regulated by law. However, students do not always obtain the same level of experience nor do the same jobs in each company. This research is aimed at analyzing the handling of Social Science Faculty of Public Administration students’ internship in private companies, Padang State University by using the descriptive qualitative method. This research reveals that some companies have not yet implemented students’ internship as one of the programmes for corporate social responsibility.